2021
DOI: 10.1007/s11042-021-11670-w
|View full text |Cite
|
Sign up to set email alerts
|

Generative adversarial network (GAN) and enhanced root mean square error (ERMSE): deep learning for stock price movement prediction

Abstract: The prediction of stock price movement direction is significant in financial circles and academic. Stock price contains complex, incomplete, and fuzzy information which makes it an extremely difficult task to predict its development trend. Predicting and analysing financial data is a nonlinear, time-dependent problem. With rapid development in machine learning and deep learning, this task can be performed more effectively by a purposely designed network. This paper aims to improve prediction accuracy and minim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Eachempati et al (2021) have also shown that the deep neural networks outperform the traditional methods of predicting the accounting disclosure, another type of financial behaviour that has gained considerable attraction from the deep learning applications (Almagtome, 2021). Another aspect of risk behaviour that was detected using such techniques is the detection of fraudulent reviews for online marketing websites (Kumar et al, 2022a(Kumar et al, , 2022b. Kumar et al, (2022aKumar et al, ( , 2022b examined the different pre-processing and feature engineering techniques to extract both reviews and review-centric features and showed that unifying these features in ML classifiers resulted in better detection of fraudulent reviews than the contemporary methods.…”
Section: Deep Learning Applications In Operation Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Eachempati et al (2021) have also shown that the deep neural networks outperform the traditional methods of predicting the accounting disclosure, another type of financial behaviour that has gained considerable attraction from the deep learning applications (Almagtome, 2021). Another aspect of risk behaviour that was detected using such techniques is the detection of fraudulent reviews for online marketing websites (Kumar et al, 2022a(Kumar et al, , 2022b. Kumar et al, (2022aKumar et al, ( , 2022b examined the different pre-processing and feature engineering techniques to extract both reviews and review-centric features and showed that unifying these features in ML classifiers resulted in better detection of fraudulent reviews than the contemporary methods.…”
Section: Deep Learning Applications In Operation Researchmentioning
confidence: 99%
“…Another aspect of risk behaviour that was detected using such techniques is the detection of fraudulent reviews for online marketing websites (Kumar et al, 2022a(Kumar et al, , 2022b. Kumar et al, (2022aKumar et al, ( , 2022b examined the different pre-processing and feature engineering techniques to extract both reviews and review-centric features and showed that unifying these features in ML classifiers resulted in better detection of fraudulent reviews than the contemporary methods. Furthermore, using deep learning techniques and text mining Huang et al (2022) provided a more accurate estimate of financial distress for beneficiaries and investors than classical machine learning algorithms.…”
Section: Deep Learning Applications In Operation Researchmentioning
confidence: 99%
“…In keeping with the approach taken by Ghoshal and Robert [17], the input datasets were then batched into tensors of shape (20,4). These tensors create a 20-day historical window for each input vector consisting of the Open, High, Low and Close prices of each day.…”
Section: Sequencing and Balancing The Datasetsmentioning
confidence: 99%
“…Finally, each (20,4) tensor generated (following Ghoshal and Roberts [17]) was individually normalised to ensure the visual appearance of the normalised candlestick is identical to the unscaled candlestick. The (20,4) input data tensors were stacked into one of either the training, validation or testing datasets, based on date, and consistent with the approach of Ghoshal and Roberts [17]. The resultant tensors had dimensionality (# samples in data split, 20, 4).…”
Section: Sequencing and Balancing The Datasetsmentioning
confidence: 99%
See 1 more Smart Citation